2017
DOI: 10.4236/jbcpr.2017.51003
|View full text |Cite
|
Sign up to set email alerts
|

Contractor Monitoring and Performance of Road Infrastructure Projects in Uganda: A Management Model

Abstract: An understanding of the influence of contractor monitoring on performance of road infrastructural projects in Uganda provided an impetus for this study. The objectives of the study were to: assess the relationship between contractors monitoring and performance of national road infrastructure projects and the relationship between contractor monitoring components and performance of national road infrastructure projects in Uganda. Purposive sampling was employed in selecting the procurement professionals, enginee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
3
6
0
Order By: Relevance
“…At the same time, not all contractors are committed to allocating adequate resources hence poor performance of roads in the post-delivery stage. This colloborates with the study findings of Byaruhanga and Basheka who established that project performance was affected by award of contracts to undeserving contractors due to weak systems of procurement; incompetence of staff involved in the procurement exercise; none existent contractor apparisal system; service delivery challenges due to delayed payments; weak internal M&E systems [60].…”
Section: Using the Statistical Findings Presented Insupporting
confidence: 62%
See 3 more Smart Citations
“…At the same time, not all contractors are committed to allocating adequate resources hence poor performance of roads in the post-delivery stage. This colloborates with the study findings of Byaruhanga and Basheka who established that project performance was affected by award of contracts to undeserving contractors due to weak systems of procurement; incompetence of staff involved in the procurement exercise; none existent contractor apparisal system; service delivery challenges due to delayed payments; weak internal M&E systems [60].…”
Section: Using the Statistical Findings Presented Insupporting
confidence: 62%
“…Their study was descriptive and therefore it lacked statistical strength to show the relationship and strength of the independent and dependent variables. Byaruhanga and Basheka in a study on contractor monitoring and road infrastructure projects performance in Uganda found that contractor monitoring is a predictor of road infrastructure projects' performance [60]. Mwangu and Iravo • demonstrated that project supervisors and contractors make use of monitoring instruments in the operations of their project, hence generating satisfactory degree of success [52].…”
Section: Process Monitoringmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the most important client support role is the payment for work done by a contractor in a project initiated by the client. Byaruhanga and Basheka observed that delay of contractors' payment affects timelines in delivery of services [25]. Ramachandra argues that the performance of the participants involved and the product output is dependent on the promptness and regularity of payment [19].…”
Section: Client Supportmentioning
confidence: 99%